2018
DOI: 10.2106/jbjs.17.00105
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Primary Central Chondrosarcoma of the Pelvis

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 46 publications
1
49
0
2
Order By: Relevance
“…Malignant pelvic bone tumors are among the most challenging problems in orthopedic oncology 9. It’s difficult to achieve wide marginal resection due the complex anatomy of the pelvis, potentially rendering a high risk of local recurrence and vital structures injury.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant pelvic bone tumors are among the most challenging problems in orthopedic oncology 9. It’s difficult to achieve wide marginal resection due the complex anatomy of the pelvis, potentially rendering a high risk of local recurrence and vital structures injury.…”
Section: Discussionmentioning
confidence: 99%
“…Zu der intermediären Gruppe gehört aufgrund des lokal aggressiven Wachstumsmusters auch der atypische kartilaginäre Tumor (ACT) der Extremitäten [9]. Während in der WHO-Klassifikation von 2013 der Begriff "Chondrosarkom Grad I" komplett durch "ACT" ersetzt und in die intermediäre Gruppe eingeordnet wurde, werden in der neuen WHO-Klassifikation von 2020 beide Begriffe in Abhängigkeit von der Lokalisation verwendet [6,10]: Bei Lokalisation im Extremitätenskelett (lange und kurze Röhrenknochen) werden die Tumoren als ACT bezeichnet und der intermediären Gruppe zugeordnet; bei Lokalisation im Achsensekelett (einschließlich Becken und Schädelbasis) werden die Tumoren bei gleicher Histologie als Chondrosarkome Grad I bezeichnet und der malignen Gruppe zugeordnet, um das differente biologische Verhalten abzubilden [11,12].…”
Section: Who-klassifikationunclassified
“…Man unterscheidet zwischen den häufigeren konventionellen Chondrosarkomen und selteneren Subtypen (▶ Tab. 3; ▶ Abb 11,12)…”
unclassified
“…According to the literature, the local recurrence rate of pelvic CS is 18–45% [ 7 9 , 15 , 20 23 ]. In this study, the local recurrence rate of the primary and secondary CS group were 37.0 and 34.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prognosis of patients in the secondary CS group was significantly better than that in the primary group, with a 5-year survival rate of 91.6 and 57% ( P = 0.003), respectively, which is consistent with the results of Ozaki et al [ 19 ]. Although it has been reported that the prognosis of CS is related to surgical resection margin [ 15 , 20 , 21 ], tumor size [ 20 ], age [ 22 ], local recurrence [ 22 ], surgical type [ 9 ], tumor stage [ 15 ], and tumor location [ 9 , 21 ]. However, in this study, we conducted a multivariate analysis of all patients with pelvic CS and found that pathological tumor grade, but not tumor type (primary and secondary), was an independent risk factor for prognosis (Table 5 ).…”
Section: Discussionmentioning
confidence: 99%